Neurocognitive Outcomes After Extracranial Surgery and General Anesthesia in Patients with a History of Mild-to-Moderate Traumatic Brain Injury: Systemic Review and Meta-Analysis - Zeeshan A. Khan; Tahiris A. Duran; Dewan Md. Sumsuzzman; Ling-Sha Ju; Christoph N. Seubert; Anatoly E. Martynyuk (Biology, 2025)
Accelerated neurocognitive decline associated with surgeries under general anesthesia (GA), a phenomenon referred to as postoperative neurocognitive disorder (PND), is a significant public health concern. It not only poses inherent risks but may also contribute to the development of other neurodegenerative disorders. We systematically searched five databases for studies examining cognitive function in patients with mild-to-moderate TBI with (participant) or without (control) subsequent extracranial surgeries/GA. A random effects model was applied to calculate mean differences (MDs) and 95% confidence intervals (CIs). Five outcomes were analyzed post hoc: trail-making tests A and B (TMT-A/B), Glasgow Outcome Scale–Extended (GOSE), and length of stay (LOS) in intensive care units (ICUs) and hospitals. Five studies met the criteria for our meta-analysis. Patients with a history of mild-to-moderate TBI who underwent extracranial surgeries/GA exhibited worse outcomes in TMT-A [MD = 2.04; CI 0.38–3.70; p = 0.016] and TMT-B [MD = 16.59; CI 9.58–23.60; p < 0.001]. Differences in the ICU and hospital LOS and GOSE between the study groups were insignificant. Our results suggest that extracranial surgeries/GA may worsen neurocognitive outcomes without affecting functional recovery in mild-to-moderate TBI patients. Given the limited number of studies identified and the high incidence of TBI, more research on PND in TBI patients is warranted.